1996
DOI: 10.1007/s004600050008
|View full text |Cite
|
Sign up to set email alerts
|

Melting of Lennard-Jones clusters in confined geometries

Abstract: The melting of Lennard-Jones (argon) clusters of various size (N"500 to 10000 atoms), confined in a rigid matrix, is studied by molecular dynamics simulations. For spherical clusters we show the existence of a cluster size below which the dependence of the melting temperature cannot be described by the classical GibbsThompson equation. We also provide evidence of the formation of a quasi-liquid layer at the surface of mesoscopic clusters. A good agreement is found between the theoretical model due to Celestini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 14 publications
5
26
0
Order By: Relevance
“…This result shows that the validity of the Kelvin equation breaks down for pores having a diameter smaller than D ∼ 18σ . This value is consistent with previous studies which have shown that the Kelvin equation becomes inaccurate for pore sizes below 16σ (Fisher and Israelachvili 1981;Walton and Quirke 1989;Celestini et al 1996;Celestini 1997). We note that the condensation pressures found in the GCMC simulations can be fitted using the modified Kelvin equation provided the use of a unreasonably large Tolman length 2δ ∼ 2 nm (∼6.5σ ).…”
Section: Adsorptionsupporting
confidence: 88%
“…This result shows that the validity of the Kelvin equation breaks down for pores having a diameter smaller than D ∼ 18σ . This value is consistent with previous studies which have shown that the Kelvin equation becomes inaccurate for pore sizes below 16σ (Fisher and Israelachvili 1981;Walton and Quirke 1989;Celestini et al 1996;Celestini 1997). We note that the condensation pressures found in the GCMC simulations can be fitted using the modified Kelvin equation provided the use of a unreasonably large Tolman length 2δ ∼ 2 nm (∼6.5σ ).…”
Section: Adsorptionsupporting
confidence: 88%
“…One of the most pronounced manifestations of change of thermodynamic properties observed in nanosized crystalline systems is the effect of reduction of the melting temperature of free nanocrystals [1][2][3][4][5][6][7][8][9]. So the principal problem of statistical description of thermodynamics of nanocrystals is elucidation of the mechanism of size effect on statistical characteristics of atoms in such systems.…”
Section: Discussionmentioning
confidence: 99%
“…Later, it was also established that this phenomenon has universal nature. It is inherent in any crystalline matter: metallic and semiconductor nanocrystals [2][3][4][5], rare gas [6,7] and ionic solids. It should be noted that depression of the melting point is observed only in free nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…1 gives an example to confirm the validity of Eq. (8) where the earliest [20] and the latest [2] experimental results with different experimental techniques and computer simulation results [21] of Au are shown. Eq.…”
Section: Modelmentioning
confidence: 99%
“…(6) where the experimental results [2,20] are predicted with d ¼ 1 while the computer simulation results [21] are done with d ¼ 0: This is because only the computer simulation may guarantee a free surface of nanocrystals. For both experimental results, the particles are either coated with porous silica shells [2] or deposited on substrate having an island shape [21], which leads to a quasi-dimension of one [9].…”
Section: Modelmentioning
confidence: 99%